Quarto molar retido: a importância do diagnóstico precoce - Fardin, Angélica Cristine [UNESP]; Gaetti-Jardim, Ellen Cristina [UNESP]; Aranega, Alessandra Marcondes [UNESP]; Jardim Júnior, Elerson Gaetti [UNESP]; Garcia Júnior, Idelmo Rangel [UNESP] (My University, 2011)
Introductions: A supernumerary tooth is one that is additional to the normal series and can be found in almost any region of the dental arch. Its etiology is not fully understood. With regard to its prevalence, it occurs more commonly in permanent dentition and twice as often in men than in women. Supernumerary teeth are classified according to their morphology and location. Their presence can cause problems such as failure of eruption, displacement of teeth, crowding and odontogenic cysts and tumors. The diagnosis is usually by routine radiographs, for the majority of such teeth are impacted and asymptomatic. Objective and Case report: The purpose of this study was to make a brief review of the relevant literature and report one clinical case of the female patient, 23 years, melanoderma, featuring three quarters molars. Final considerations: The early diagnosis proved to be important for the resolution of the case in order to minimize or even prevent the development of complications and thus establish a proper plan of treatment.

Dente supranumerário é aquele que excede a série normal, podendo ocorrer em ambos os arcos dentá- rios. Sua etiologia não é completamente entendida. Em relação a sua prevalência, ocorre mais na dentição permanente e duas vezes mais nos homens que nas mulheres. Os dentes supranumerários são classificados de acordo com sua morfologia e localização. A presen- ça desses dentes pode causar problemas, como falhas na erupção, deslocamento de dentes, apinhamentos, cistos e tumores odontogênicos. O diagnóstico é realizado geralmente por meio de radiografias de rotina, pois a maior parte desses dentes está inclusa e é assintomática. Objetivo e relato do caso: Este trabalho teve como objetivo realizar uma breve revisão de literatura e relatar um caso clínico de paciente do sexo feminino, 23 anos, melanoderma, com três quartos molares. Considerações finais: O diagnóstico precoce mostrou ser importante para a resolução do caso minimizar ou prevenir o aparecimento de complicações e estabelecer um adequado plano de tratamento.
Fourth molar: the importance of early diagnosis
Keywords: Buccal surgery; Supernumerary teeth; Impacted tooth; Cirugia bucal; Dente impactado; Dente supranumerário